Swedish Riksbank notes and Enskilda bank notes: Lessons for digital currencies - Ben Siu-Cheong Fung; Scott Hendry; Warren E. Weber (Bank of Canada, 2018)
This paper examines the experience of Sweden with government notes and private bank notes to determine how well the Swedish experience corresponds to that of Canada and the United States. Sweden is important to study because it has had government notes in circulation for more than 350 years, and it had government notes before private bank notes. Several differences between the experience of Sweden and that of Canada and the U.S. emerge. (i) Swedish bank notes were safe; in some cases, those of Canada and the U.S. were not. (ii) At certain times, Swedish government notes were not safe; government notes in Canada and the U.S. always were. (iii) Swedish private bank notes were a uniform currency without government intervention. Uniformity required government intervention in Canada and the U.S. (iv) Private notes and government notes coexisted in all three countries until governments took actions to drive private bank notes out of circulation. Using the experience of the three countries, the paper concludes that fiduciary digital currencies will likewise not be perfectly safe without government intervention. Further, the introduction of government digital currency will not drive out existing private digital currencies nor will it preclude private digital currencies from entering the market. Government intervention likely will be required for private and government digital currencies to be a uniform currency.
Keywords: E41; E42; E58; 330; Bank notes; Financial services; Digital currencies